Assessment of salt leaching management in saline soils with MACRO model - Hamid Zare; Mohammadreza Khaledian; Mahmoud Shabanpour; Amir Malekpour (علوم و مهندسی آبیاری)
Today, in many parts of the world, water and soil resources are facing the threat of salinization. Several researches has been done for the desalination of water and soil resources. One of these proposed solutions is leaching. There are several leaching methods which should be studied for each area. The present paper studies the saline soil of Nazarabad area, Iran using two types of saline and conventional water of the region and three different volumes of water (one, three, and five times the pore volume) in both continuous and alternate modes under frozen and non-frozen conditions with three replications. Then, the movement of salt was simulated by the MACRO model. The amount of salinity in drain water was measured during the experiments. The results showed that the conventional water managed to reduce soil salinity and solute concentration in the leaching experiments. Accordingly, the frozen treatments continuously irrigated with conventional water outperformed other treatments in terms of achieving minimum soil salinity (ECe<1 dS/m). Similarly, less water can be used in these treatments to reach the minimum ECe according to the irrigation scheduling predicted by the MACRO model i.e. 3.5 pore volume. At last, it was found that these soils did not require CaCl2 for correction.